The true systematic status of Liolaemus misleali Donoso Barros and Cei, 1971, from Northern Patagonia, Argentina (Reptilia, Iguanidae) - Cei, José Miguel Alfredo María (1987)
The taxonomic status of the poorly known Patagonian Lizard Liolaemus ruizleali has been revised according to its only extant holotype and paratypes. It is a composite species: the holotype and two paratypes belong to Liolaemus rothi Koslowsky, 1898, the other four paratypes to Liolaemus kingi somuncurae Cei and Scolaro, 1981. The synonymic list of these latter species is readjusted.